한의 개인건강기록 플랫폼 구축에 관한 연구 - 서진순(Jin Soon Seo); 김안나(An Na Kim); 김상현(Sang Hyun Kim); 이승호(Seung Ho Lee); 남보령(Bo Ryeong Nam); 이명구(Myung Ku Lee); 장현철(Hyun Chul Jang) (동의생리병리학회지, 2016)
The information relating to the health of person has been increasing. The information is such as medical information and personal health record and the information collected by utilization and dissemination of mobile devices. Therefore, the interest and demand for systems that can integrate and manage the Personal Health Record(PHR) is increasing. Quantity and quality of information that is collected from the patient can have a major impact on the diagnosis and treatment of Korean Medicine(KM) in clinical practice. Because closely observe the usual clinical symptoms of patients to utilize the treatment. But if the interview when memories are not sure of the correct answer does not get much easier to find exactly the symptoms. So when recording original symptom(素證) and daily subjective symptom can be helpful for care. Therefore, the personal health care services that can record and manage and own is necessary based on KM. In this paper, we propose Korean Medicine Personal Health Record Platform(KM PHR Platform). We have selected the significant symptoms that mean to the personal records from symptom information required for diagnosis in KM. And classifying and scoring as the symptoms were used as personal health care indicators. And significant symptoms were easily configure a screen that can be recorded. simple operation is recorded as a symptom. It was designed to reflect these functions. So KM PHR Platform helps to Personal health care. Doctor may be able to help in the diagnosis and prognosis observation by reference to shared symptom. We look forward to a variety of health services based on KM using a symptom, a medical record, personal health device information.